Analysis and Design Of New Student Admission Systems On MTS AL MUHTADIIN - Husain, Al; Hidayatullah, Agus (Aptisi Transactions On Technopreneurship (ATT), 2019)
MTs Al-muhtadiin is the first private vocational school in the sub-district of Sukadiri, at the beginning of the opening of this school, it received quite a positive response with proven opening in 2017 around 62 students registered themselves as students at MTs Al-Muhtadiin. The new student registration system at MTs Al-Muhtadiin is already running effectively and efficiently. In analyzing the running system used the method of analysis and depiction of the system using UML (Unified Modeling Language) and in data collection used interview, observation and literature study methods. The results of the analysis of the system that runs in the admission of new students at MTs Al-Muhtadiin are still running manually with the help of Microsoft Excel in the process of making reports.